Developing a 3D Virus Attack Simulation in Unity: A Case Study for Healthcare Education - Fortilla, Zeny Arsya; Jazuli, Muhammad Syauqi (Gameology and Multimedia Expert, 2024)
Virus Attack 3D is a 3D platformer game that visualizes humans running to avoid Coronavirus attacks encountered on a path with increasing speed at each level. The player's character dies upon collision, but the game continues with increasing score and level if the player successfully avoids the viruses. This research aims to design Virus Attack 3D, incorporating health-themed education. The application is built using the C# programming language in the Unity application for a more strategic experience. Virus Attack 3D is a platformer game that serves as the research output. The entertaining Virus Attack application offers a game enjoyable for all ages, training players' spontaneous response and dexterity in overcoming challenges while providing entertainment on desktops in single-player mode.